2003
DOI: 10.1242/jcs.00294
|View full text |Cite
|
Sign up to set email alerts
|

Nonerythroid αII spectrin is required for recruitment of FANCA and XPF to nuclear foci induced by DNA interstrand cross-links

Abstract: The events responsible for repair of DNA interstrand cross-links in mammalian cells, the proteins involved and their interactions with each other are poorly understood. The present study demonstrates that the structural protein nonerythroid α spectrin (αSpIIΣ*), present in normal human cell nuclei, plays an important role in repair of DNA interstrand cross-links. These results show that αSpIIΣ* relocalizes to nuclear foci after damage of normal human cells with the DNA interstrand cross-linking agent 8-methoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
202
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(221 citation statements)
references
References 67 publications
19
202
0
Order By: Relevance
“…Accordingly, disruption of the FA pathway results in persistence of DNA breakage (Rothfuss and Grompe 2004). It is interesting to note that although XPF/ERCC1 has been reported to colocalize with FANCA, suggesting it may function in the FA pathway (Sridharan et al 2003), XPF/ERCC1 mutant cells demonstrate normal FANCD2 monoubiquitination (R.D. Kennedy and A.D. D'Andrea, unpubl.).…”
Section: Recruitment Of Dna Repair Proteinsmentioning
confidence: 99%
“…Accordingly, disruption of the FA pathway results in persistence of DNA breakage (Rothfuss and Grompe 2004). It is interesting to note that although XPF/ERCC1 has been reported to colocalize with FANCA, suggesting it may function in the FA pathway (Sridharan et al 2003), XPF/ERCC1 mutant cells demonstrate normal FANCD2 monoubiquitination (R.D. Kennedy and A.D. D'Andrea, unpubl.).…”
Section: Recruitment Of Dna Repair Proteinsmentioning
confidence: 99%
“…Alpha spectrin is identified at the nuclear envelope [30]. More recently, Lambert and colleagues demonstrated that SpαII is involved in DNA repair in the nucleus [19,20,48,49] (Tab. 2).…”
Section: Suggested Functions In Nucleimentioning
confidence: 99%
“…Indeed, SpαII was described as a component of a chromatin-associated complex that was involved in the repair of DNA inter-strand crosslinks, and was identified as being a direct binding partner of the DNA-repair proteins, FANCA and FANCC [48]. Subsequent studies have shown that SpαII binds directly to DNA inter-strand cross-links [18,49]. SpαII is localized to multiple nuclear foci along with two DNA-repair proteins (FANCA and XPF) to which it binds directly [49].…”
Section: Suggested Functions In Nucleimentioning
confidence: 99%
“…73,74 Furthermore, XPF interacts with the FANC-A, Msh2, and non-erythroid α Spectrin αSPIIΣ proteins, further demonstrating its role in the removal of interstrand crosslinks. [75][76][77][78] A recently identified interesting role for XPF is its interaction with the telomere elongation factor TRF2. This factor is responsible for the conversion of telomeric TTAGGG repeats tracts to T-loop structures that protect the telomeres from inadvertent double-strand break repair.…”
Section: Cutting It Out: Xpg and Xpfmentioning
confidence: 99%